In-vitro study on antibacterial, cytotoxicity and pH evaluation of propolis, piper betle and calcium hydroxide as intracanal medicaments - Rafi, Ayesha (2021)
Natural products such as propolis and Piper betle have shown antibacterial activity against resistant oral pathogens such as Enterococcus faecalis (E. faecalis) and are considered to be less toxic compared to calcium hydroxide [Ca(OH)2]. However, their role as an intracanal medicament, antibacterial activity against E. faecalis, cytotoxicity, and acidic or basic nature has not been explored. This study was aimed to evaluate and compare the antibacterial activity of E. faecalis, acidic/alkaline nature, and cytotoxic effect of propolis, Piper betle, and Ca(OH)2 on human periodontal fibroblasts (HPdLF). Five test materials were used: ethanolic extract of propolis (EEP); ethanolic extract of Piper betle (EEPB); aqueous extract of propolis (WEP); aqueous extract of Piper betle (WEPB) and Ca(OH)2. After the growth of the E. faecalis strain (ATCC 29212), broth dilution testing was performed to define the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Cytotoxicity was determined by MTT assay on HPdLF with the concentration range of 100mg/ml to 0.78mg/ml for all the test materials. The data were analysed by Kruskal-Wallis and Spearman’s correlation test at the level of significance set at 0.05 and 0.01. The lowest and best MIC and MBC were reported at similar concentration for EEP and EEPB at 3.12 mg/ml and 6.25 mg/ml followed by WEPB and Ca(OH)2 with MIC at 50 mg/ml and MBC at 100 mg/ml. The highest MIC and MBC were reported for WEP at 200 mg/ml and 400 mg/ml. The mean pH for propolis and Piper betle were found to be acidic, whilst Ca(OH)2 was alkaline. MTT assay revealed that EEPB, EEP, WEP, and WEPB were not toxic to HPdLF compared to the negative control. The fifty percent inhibitory concentration (IC50) for EEPB, EEP, WEP, and WEPB was estimated above 100 mg/ml. However, Ca(OH)2 was toxic at the concentration of 100 mg/ml and 50 mg/ml, and IC50 was found at 43.53 mg/ml. No correlation between pH and concentration for propolis was found. However, an inverse correlation was reported for Piper betle and a direct correlation was reported for Ca(OH)2 (p<0.01). The pH was not related to the percentage cell viability of fibroblasts for all the groups except in Ca(OH)2 which reported inverse correlation (p<0.01). The propolis and Piper betle extracts had effective antibacterial activity against E. faecalis, acidic, and less cytotoxic to HPdLF as compared to Ca(OH)2.